Advances in Classification and Treatment of Non-Hodgkin Lymphoma: Mantle Cell. Issue 4 (July 2020) - Rule, Simon; Johns, Sophie
Abstract : Abstract: Mantle cell lymphoma is a rare, aggressive, and largely incurable form of non-Hodgkin lymphoma. There are a number of well-characterized prognostic features but nothing that can help guide therapy. Treatment with chemotherapy is generally effective in the short term, but relapse is inevitable and subsequent treatment is challenging. The use of Bruton tyrosine kinase inhibitors, however, has transformed practice. These agents are highly active in relapsed disease and are very well-tolerated drugs. Chemotherapy-free combinations using Bruton tyrosine kinase inhibitors look very exciting and will likely evolve to be part of frontline care in the future.